College Course Shutouts - Kevin J. Mumford; Richard W. Patterson; Anthony Yim (Center for Economic Studies and ifo Institute (CESifo), 2024)
What happens when college students are not able to enroll in the courses they want? We use a natural experiment at Purdue University in which first-year students are conditionally randomly assigned to oversubscribed courses. Compared to students who are assigned a requested course, those who are shut out are 40% less likely to ever take the oversubscribed course and 30% less likely to ever take a course in the same subject. While a course shutout is equally likely to occur to female and male students who requested the course, shutouts are much more disruptive for female students. In the short run, shutouts decrease the credits female students earn as well as their GPA. In the long-run, shutouts increase the probability female students drop out of school in the first year, decrease the probability they choose majors in STEM fields (Science, Technology, Engineering, and Math), decrease cumulative GPA, and decrease the probability of graduating within four years. In contrast, shutouts have no effects on short-run credits earned, dropout, majoring in STEM, cumulative GPA, or four-year graduation for male students. Shutouts do have one large measurable long-run impact on male students—shutouts significantly increase the probability that men choose a major from the business school.
Keywords: I23; J16; J24; 330